THE Analysis of Prostitute Case in the Burning Sun Chat Room - Zam, Nurul Hikmah Alfilai; Sawirman, Sawirman; Usman, Fajri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
This research aims to analyze chat evidence of prostitution cases found in the disclosure of the Burning Sun case. Several well-known K-pop idols and top Korean entertainment companies are involved in this case. Forensic language examination is used for this research to examine the evidence. The study uses a method of collecting, analyzing, and interpreting chat data from various sources that are relevant to the case. In the chat evidence, it was found the role of each participant involved in prostitution. Linguistic forensics analysis identifies the hidden messages, motives, and roles of every individual in the conversation. These findings have a material impact on the legal proceedings and investigations in connection with the Burning Sun case. It also provides insight into how forensic linguistic techniques can be used to identify and analyze chat evidence in a legal context. Therefore, this research provides a deeper understanding of the role of language in criminal proceedings involving famous figures such as K-pop idols and underlines the importance of linguistic analysis in law enforcement.